(untitled) (Research, Society and Development, 2022)
Pyometra is the endometrial disorder of greatest clinical importance in small animals. The realization of studies with the purpose of obtaining epidemiological data related to the occurrence of pyometra in bitches are fundamental. The objective was to determine epidemiological indicators of canine pyometra using the statistical method of principal component analysis and to characterize the set of parameters that facilitate the diagnosis and a possible clinical-epidemiological profile, through the casuistry attended in university veterinary hospitals in the northeastern region of Pará. A total of 142 medical records in two university veterinary hospitals were consulted. A total of 18 variables were analyzed using principal component analysis (PCA) and descriptive statistics. The PCA identified three groups of epidemiological indicators that together explained 71.05% of the variability of the data. The first group (abdominal pain, abdominal distension, critical condition and leukocytosis), the second (apathy, anorexia, pyometra type, and vaginal discharge) and the third (age, race, parity and pseudocyesis). It was observed that 47.7% of the bitches were five to 10 years old, 63.8% were of undefined breed and 62.4% were nulliparous (p<0.05). The pyometra of the open type presented a frequency of 82.4% (p<0.05). The variables pain, abdominal distension and leukocytosis are indicators of severe stage disease. The variables apathy, anorexia/hyporexia and vaginal secretion are indicators of disease in mild stage and the variables age and race act as epidemiological indicators of predisposition. Moreover, it was identified that the clinical-epidemiological profile of affected animals is of middle-aged, non-breed, nulliparous bitches with open pyometra.